Aplicativo mobile para controle de agenda em consultório odontológico - Mathias, Guilherme Pellegrini (2017)
The control of the schedule as of doctors, dentists and physiotherapists, helps in optimizing the use of the time of these professionals and, mainly, to avoid patients (clients) wait to be attended. Considering the importance of agenda control for certain professionals and the wide use of mobile devices, this work presents the development of a mobile application for use in dental offices, including functionalities such as: scheduling, patient registration data, financial data and record of anamnesis. The application also has other features such as the possibility of attaching radiographic exams and questionnaires and issuing reports containing patients' historical data. The application developed presents the use of the technology of the mobile devices (cell phones and tablets) as a way to facilitate and speed up the work performed in the offices, providing the user with an easy to use application, but at the same time add technological resources in Terms of functionality.